The Role of Omni-Channel Marketing, Personalization, Customer Experience, and Brand Trust on Repurchase Intention - Ramadhan, Fahad (International Journal of Business, Law, and Education, 2026)
This study aims to analyze the role of omni-channel marketing, personalization, customer experience, and brand trust on repurchase intention. The research employed a quantitative approach using explanatory research design to examine the relationships among the variables. Data were collected through questionnaires distributed to consumers who had experience purchasing products or services through integrated online and offline channels. A total of 230 valid responses were analyzed using multiple linear regression analysis with the assistance of IBM SPSS Statistics. The findings reveal that omni-channel marketing, personalization, customer experience, and brand trust have positive and significant effects on repurchase intention, both partially and simultaneously. Among the independent variables, customer experience was identified as the most dominant factor influencing repurchase intention. The results indicate that consumers are more likely to make repeat purchases when companies provide seamless channel integration, personalized services, satisfying experiences, and trustworthy brand performance. Furthermore, the coefficient of determination shows that the four variables collectively explain a substantial proportion of the variation in repurchase intention. This study contributes to the development of marketing management literature by providing empirical evidence regarding the importance of integrated customer relationship strategies in the digital era. The findings also offer practical implications for businesses to improve customer retention by enhancing omni-channel systems, delivering personalized interactions, creating positive customer experiences, and strengthening brand trust.